Biodismantling, a Novel Application of Bioleaching in Recycling of Electronic Wastes - Benjamin Monneron-Enaud; Oliver Wiche; Michael Schlömann (Recycling, 2020)
Electronic components (EC) from waste electrical and electronic equipment (WEEE) such as resistors, capacitors, diodes and integrated circuits are a subassembly of printed circuit boards (PCB). They contain a variety of economically valuable elements e.g., tantalum, palladium, gold, and rare earth elements. However, until recently there has been no systematic dismantling and recycling of the EC to satisfy the demand for raw materials. A problem connected with the recycling of the EC is the removal of the components (dismantling) in order to recover the elements in later processing steps. The aim of the present study was to develop a new technique of dismantling using bioleaching technology to lower costs and environmental impact. In triplicate batch experiments, used PCBs were treated by bioleaching using an iron-oxidizing mixed culture largely dominated by Acidithiobacillus ferrooxidans strains supplemented with 20 mM ferrous iron sulfate at pH 1.8 and 30 °C for 20 days. Abiotic controls were treated by similar conditions in two different variations: 20 mM of Fe2+ and 15 mM of Fe3+. After 20 days, successful dismantling was obtained in both the bioleaching and the Fe3+ control batch. The control with Fe2+ did not show a significant effect. The bioleaching condition presented a lower rate of dismantling which can partially be explained by a constantly higher redox potential leading to a competition of solder leaching and copper leaching from the printed copper wires. The results showed that biodismantling—dismantling using bioleaching—is possible and can be a new unit operation of the recycling process to maximize the recovery of valuable metals from PCBs.